(untitled) (Cambridge, UK, 1999)
The book addresses the impact of culture when learning interact, speak, construct meaning, and write in a second language, and within the sociocultural paradigms specific to a particular languag and its speakers. It also offers an important to the field of second language acquisition.
Keywords: Language and culture,Second language acquisition,Language and culture; Study and teaching,Study and teaching